Sub-state Policies on Immigrant Transnationalism: Varied Motivations behind Destination Country Political Agendas - Sánchez-Montijano, Elena (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
While the literature has shown the importance of the destination country in shaping the relationships immigrants maintain with their country of origin, the role of sub-state authorities is yet to be defined. This article analyses the characteristics and motivations behind transnational migration policies carried out by sub-state authorities through case studies of the Catalonia region and the city of Barcelona. Using data collected through in-depth interviews and a qualitative analysis of documents, the results show that city and regional authorities recognise transnational activities as a common good, but while certain transnational economic, political, and socio-cultural activities are given governmental support, others are not. Different political motivations lie behind transnational migration policies. This article adds two new hypotheses to the accepted in the literature. First, public authorities recognize an economic and political benefit for themselves in supporting migrant transnationalism. Second, these same authorities perceive such actions as complementary tools in the process of identity construction, such as that currently taking place in Catalonia.
Keywords: transnational activities; sub-state authorities; public policies; identity construction; migrants